Hydrogenation of CO2 to light olefins on CuZnZr@(Zn-)SAPO-34 catalysts: Strategy for product distribution. (1st March 2019) - Chen, Jingyu; Wang, Xu; Wu, Dakai; Zhang, Jianli; Ma, Qingxiang; Gao, Xinhua; Lai, Xiaoyong; Xia, Hongqiang; Fan, Subing; Zhao, Tian-Sheng
Graphical abstract: Composite catalysts CZZ@(Zn-)SAPO-34 with core-shell structure were prepared and applied to hydrogenation of CO2 to light olefins via tandem reaction of methanol synthesis and methanol dehydration. Second hydrogenation of primary products are restrained due to reduced contact interface and acidity under low concentration of methanol intermediate. Olefin selectivity of 72% was achieved over CZZ@Zn-SAPO-34 (4/1) at H2 /CO2 of 3, 6000 h −1, 400 °C and 2 MPa. Highlights: Core-shell CuZnZr@(Zn-)SAPO-34 catalysts for light olefin synthesis from CO2 hydrogenation. Reduced acidity of SAPO-34 by Zn addition for low concentration of intermediate methanol. Restraining secondary hydrogenation of primary olefins. Abstract: Composite catalysts containing CuZnZr(CZZ) and SAPO-34 were prepared and applied to the hydrogenation of CO2 to light olefins via the tandem reactions of methanol synthesis and methanol to olefins. The product selectivity was significantly affected by the composite methods, mass ratio of CZZ and SAPO-34 and the acid density of SAPO-34. Compared with physically mixed CZZ/SAPO-34, assembled core–shell CZZ@SAPO-34 increased the selectivity of olefins and inhibited CH4 formation, due to reduced contact interface and hydrogenation ability on the metal sites. Furthermore, reducing the acidity of SAPO-34 by Zn addition greatly restrained secondary reactions of the primary olefins. A high olefin selectivity of 72% was achieved over CZZ@Zn-SAPO-34 (4/1) at H2 /CO2 of 3, 6000 h −1, 400 °C and 2 MPa. Because the concentration of intermediate methanol remained low level during the reaction and small amount of CZZ was doped into Zn-SAPO-34, a large amount of C3 and C4 hydrocarbons were formed owing to the hydrogenation and hydrogen transfer reactions of primary C2 –C4 olefins.